STUDENTS’ DIFFICULTIES IN TRANSLATING ENGLISH TEXT - Arono Arono; Nadrah Nadrah (JOALL (Journal of Applied Linguistics and Literature), 2019)
Nowdays, there are many translation problems although software application to assist translation are available. The objectives of this research were to identify types of error in translation, students’ difficulties in translating text, and factors which influence students’ error in translating in English department of State Institute for Islamic Studies Bengkulu. This research  used descriptive quantitative method. The results of this research showed that students’ difficulties in translating English text, were elliptical errors (67.29%), idioms (87.5%), and textual meaning (73.54).  The difficulties of students in translating were  lack of vocabulary (87,50%), difficult translating Islamic texts (75,00%), literary works (66,66%), and grammatical issues (62,50%). Then, the factors affected students’ error in translation were ignorance of ellipsis; unable to identify ellipsis, idiom, and lexical meaning; lack of strategy in translating ellipsis,  idiom, and lexical meaning; translating words per word; most students lack a strong background on the content of the text. It was concluded that the students got three types of error in transalation, four points difficulties in translation, and six factors which influence the students’ error in translation.Keywords: Translation, difficulties, and English text